Mutation location on the RAS oncogene affects pathologic features and survival after resection of colorectal liver metastases. Issue 4 (13th October 2016) - Frankel, Timothy L.; Vakiani, Efsevia; Nathan, Hari; DeMatteo, Ronald P.; Kingham, T. Peter; Allen, Peter J.; Jarnagin, William R.; Kemeny, Nancy E.; Solit, David B.; D'Angelica, Michael I.
Abstract : BACKGROUND: In the past 3 decades, a better understanding of gene mutations and their role in carcinogenesis has led to improvement in our ability to treat patients with metastatic disease. The objective of the current study was to determine whether the location of a driver mutation within an affected gene impacts the biology of metastatic colorectal cancer. METHODS: DNA was collected from 165 randomly selected specimens of patients who underwent margin‐negative resection of colorectal liver metastases with curative intent. Sequenom analysis and Sanger sequencing were used to evaluate mutations in K/NRAS, PIK3CA, BRAF, and TP53. RESULTS: BRAF mutation was associated with early recurrence and death, whereas no impact of TP53 or PIK3CA mutation was identified. Although K/NRAS mutation was associated with worse survival in this cohort, this difference was no longer evident when those who had received anti‐EGFR therapy were excluded. When stratifying patients according to the exon on which K/NRAS was mutated, there were dramatic differences in both survival and pathologic features. Exon 4 mutations were associated with large, solitary metastases occurring at long disease‐free intervals compared with exon 3 mutations, which presented with small, numerous lesions. Patients who had exon 4 mutations recurred infrequently and had significantly longer survival compared with those who had wild type or other mutations. CONCLUSIONS: By using this model of curative‐intent, margin‐negative resection in patients at high risk of recurrence, the authors were able to establish a link between mutation location within the K/NRAS gene and the biology of metastatic colorectal cancer. Cancer 2017;123:568–575. © 2016 American Cancer Society . Abstract : The authors sought to determine whether the location of driver mutations within the RAS oncogene impacts the biology of metastatic colorectal cancer. After stratifying patients by the exon location of mutation, dramatic differences are observed in both survival and pathologic features.